Teknik Pemanfaatan Biji Buah Pohon Raja (Pangium edule) Sebagai Bahan Makanan Oleh Masyarakat Kampung Kumurkek, Distrik Aifat, Maybrat-Papua Barat - Sepus M. Fatem; Novita Panambe; Novita Kosamah; Melanesia B. Boseran (Universitas Lambung Mangkurat, 2020)
In rural forest areas, plants and animals provide communities’ daily needs as well as marketable products that generate income for local communities. Healthy forests not only provide important ecological functions but also contribute to an indigenous population’s economy and culture. Papua is an important region in the world to study the social importance of tropical rainforests, as this vast region contains over 250 ethnic groups, most of whom depend on forest ecology for their livelihood. This research was aims to understand the process and utilization technique of Raja’s seeds (Pangium edule) as a traditional food source according to the indigenous knowledge of the Aifat people in Kumurkek, Aifat sub-District, Maybrat Regency. The study uses descriptive methods, field observations, and semi-structured interviews. Results indicate that there are six stages of Raja’s seeds processing, including seed harvesting, poaching, slicing, soaking in a river, and culminating in consumption. Tools and materials used in processing the seeds include machetes, wood, stone, and metal pans. As of now, there is no conservation scheme to preserve the Raja plant. However, the knowledge of Raja plant production is still bequeathed among relatives according to local tradition. Further research is needed in order to find other benefits of this species, such as use as a natural pesticide and other potential products that can provide additional income for the Aifat sub-District.